Associations between adiposity indicators and hypertension among children and adolescents with intellectual disability—A case–control study. Issue 5 (6th April 2020) - Wyszyńska, Justyna; Podgórska‐Bednarz, Justyna; Dereń, Katarzyna; Baran, Joanna; Czenczek‐Lewandowska, Ewelina; Leszczak, Justyna; Mazur, Artur
Abstract : Background: Adiposity is closely related to hypertension (HTN) in paediatric population. However, which adiposity indicator is most associated with HTN among children and adolescents with intellectual disability remains unknown. The aim of this study was to evaluate the associations between HTN prevalence and different adiposity indicators: body mass index (BMI) percentile, body fat percentage (BFP), waist circumference (WC), hip circumference (HC), waist‐hip ratio (WHR) and waist‐to‐height ratio (WHtR) in students with intellectual disability. Methods: Cross‐sectional study included a sample of 568 schoolchildren with intellectual disability, aged 7–18 years. Blood pressure, BMI, body composition, WC and HC were determined using standardized equipment. Results: Multivariate logistic regression showed that male gender, adolescence, high HC and excessive BFP were significant independent factors that increased risk of HTN occurrence in population with intellectual disability. Conclusions: Findings indicated that HC and BFP, in particular, may be helpful tools to detect HTN in population with intellectual disability.